Reinvesting in equity crowdfunding: The case of digital workers - Rayan Faisal A. Makki; Stefan van Hemmen (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The purpose of this study is to investigate the initial investment's motivations and study the reinvesting motivations. The results revealed differences in reinvestors' motivations of reinvestors in both winning and losing situations. Specifically, financial return and excitement motives were supported for win and loss situations, while recognition was supported for loss and pleasure in win situations. Design/methodology/approach - The impact of intrinsic and extrinsic motivations on reinvestors was tested using the structural equation model. Furthermore, the framework was analysed with survey data from a total of 355 digital workers from Amazon Mechanical Turk, one of the world's largest crowdsourcing platforms. Findings - The results indicate that there are differences in the motivations for reinvestors when they are in both winning and losing situations. Financial return and excitement motives were supported for win and loss situation, while recognition was supported in loss and pleasure in win situation. Research limitations/implications - This study makes it possible to better understand the motivations behind crowdfunding reinvestment among digital workers. To build on this work, more studies should be conducted with different samples to test the generalisability of these results. Moreover, future studies on different samples could determine whether the same motivations would hold for other investors or whether another motivation would have greater impact on these reinvestment decisions. Originality/value - While previous research on equity crowdfunding has predominantly focused on intrinsic and extrinsic motivations for participating and investing in equity crowdfunding platforms, the motives that specifically affect winning or losing situations for reinvestors have been largely overlooked.
Keywords: 330; Equity crowdfunding; Self-determination theory; Reinvesting; Serial investors